Desempenho produtivo e qualidade do leite de cabras leiteiras alimentadas com dietas contendo quatro níveis de casca de mamona - Santos, Sueli Freitas dos (2008)
To evaluate the productive performance and milk quality of dairy goats fed diets containing four levels of castor bean hulls, this research was carried out at the dairy goat sector of the Embrapa Goats, at Sobral-CE. Eight dairy goats were used, consisting of Anglo-Nubiana breed, averaging 45 kg of body weight and with approximately 60 days of nursing. The animals were housed in metabolism cages and distributed in a latin square 4 x 4 experimental design. The treatments consisted of four levels (0; 33; 67 and 100%, on a dry/fresh matter basis) of Tifton-85 grass hay substitution by castor beans hulls as roughage feed maintaining a roughage: concentrate ratio of 50:50. Each experimental period was 21 days along, divided in 14 days of adaptation and seven days of data collection. The following variables were measured: voluntary feed intake; nutrients apparent digestibility and nitrogen balance, milk production and constitution,density of milk and fatty acid profile. The substitution of Tifton-85 grass hay by castor bean hulls reduced the consumption of: dry matter, crude protein, ether extract, neutral detergent fiber, non-fibrous carbohydrates and total carbohydrates. It was not observed difference among diets digestibility coefficients. There was influence of the treatments on the digestibility coefficients, resulting in a linear reduction in nitrogen intake and excretion (fecal, urinate and milk) rates and in the nitrogen balances, with means of 27.3, 6.95, 7.90, 5.46 and 7.05%, respectively. There was a decrease in milk production,with the last two levels not differing to each other. In relation to the milk chemical composition, there was no effect of the Tifton-85 hay substitution by castor beans hulls on the crude protein, mineral matter, lactose and total dry extract, but there was an increase in fat levels in 67 and 100% substitution, not sufficient to promote changes in milk density, averaging 1.031 g/l. In relation to the effect of the Tifton 85 hay substitution by castor beans hulls on fatty acids concentration, there was no effect on the myristic (C14: 0), linoelaidic (C18: 2n6t) and conjugated linoleic (CLA 9t11) acids levels, (P<0.05), as well as the profile of polyunsaturated and saturated (AGPOL and AGESS) fatty acids. There was no effect of the treatments on unsaturated, short chain, long chain and monounsaturated fatty acids. The substitution of Tifton-85 grass hay by castor bean hulls reduced the aterogenicity index (IA) of the diet. The castor bean hulls can replace up to 33% of the Tifton-85 grass hay in dairy goats diets without causing major reductions in feed intake and digestibility and also without causing any loss in the physical-chemical composition nor in the milk production